LAS IDEAS METODOLOGICAS DE FELIX KAUFMANN - URANGA, EMILIO (Hospital General, Departamento Medecin Resesarch, CD MEXICO, DF, MEXICO, 1913)
An extensive review of Kaufmann's book: Methodology in the Social Sciences after a Spanish translation by Eugenio Imaz Uranga stresses Kaufmann's discussion of psychology and its concepts, particularly the relationship of feeling and understanding The a
REV MEX SOCIOL
Keywords: IDEAS, METODOLOGICAS, FELIX KAUFMANN; SOCIOLOGIA; SOCIOLOGIA GENERAL; METODOLOGIA